Behaviour of ten cultivars of lettuce fertilized with urban waste compost - Cristina dos Santos, Izabel; Wagner Dias Casali, Vicente; Vieira Miranda, Glauco (Pesquisa Agropecuaria Brasileira, 1998)
This work was conducted in greenhouse at the Universidade Federal de Viçosa, Brazil, in 1993, aiming to verify the behaviour of ten lettuce cultivars (Lactuca sativa L.), when fertilized with urban waste. The substrate consisted of waste compost (on a dose equivalent to 35 t/ha) and a Red-Yellow Latosol, clayey texture. The treatments were ten cultivars. The statistic model applied was in randomized block with four replications. Lettuce cultivars fertilized with urban waste compost differed among themselves in relation to the weight of leaf dry-and-fresh matter, root dry matter and concentration of Zn, Mn, K and Na in leaf dry matter. There was no difference among the cultivars in relation to the concentration of Pb and Cu in leaf dry matter. In all cultivars, the Pb concentration exceeded 0.50 μg/g of fresh matter, which is the tolerance limit for this metal in fresh leaves.